Weed control efficiency of unmanned aerial vehicle spray in replanting oil palm plantation areas - Kamalul Adham, Che Ruzlan; Shahrul Azman, Bakar; Che Ahmad Hafiz, Che Manan; Muhammad Khairul Anuar, Mohd Noor; Mohd Razman, Abd Latif; Cik Mohd Rizuan, Zainal Abidin; Mashitah, Jusoh; Muhammad Saiful, Ahmad Hamdani (Cambridge University Press, 2025)
Efficient chemical weed management considers precise application of herbicides, maximizing herbicide retention and absorption, reducing the impact of abiotic factors, and mitigating offtarget movement in order to optimize herbicide efficacy. Hence, this study assessed the employability and cost-efficiency of an unmanned aerial vehicle (UAV) for preplanting application and postemergence selective weed control of grasses infesting legume cover crops (LCCs) in an immature oil palm (Elaeis guineensis Jacq.) plantation. Field experiments were conducted in 2020 and 2021 at a research center and an oil palm replanting area in Jerantut, Pahang, Malaysia. Droplet deposition and distribution analyses revealed that the pressure at 0.25 MPa yielded better spray coverage and increased droplet counts compared with 0.15 MPa. For preplanting application, both the UAV and mist blower resulted in total weed control. Meanwhile for selective grass control in the LCCs, conventional knapsack sprayer (CKS) application provided slightly better weed control than the UAV over the 12-wk observation. However, a cost-efficiency analysis revealed that UAV spraying yielded economically favorable results for areas greater than 3,000 ha, with potential savings ranging from 4% to 28%. Furthermore, UAV spraying demonstrated superior operational efficiency and reduced working hours by 37%, water consumption by 91%, and human labor expenses by 81% compared with both conventional methods. These findings underscore the potential of UAVbased spraying for large-scale weed control in oil palm plantations and highlight its efficiency, comparable effectiveness, and cost-saving benefits.